DETERMINATION OF THE STRUCTURE OF IMPURITIES IN TRIETHYLENE GLYCOL BY NMR AND HPLC-MS/MS OF HIGH RESOLUTION - M. N. Usachev; Yu. A. Efimova; N. K. Zaitsev (Тонкие химические технологии, 2016)
The process of natural gas drying leads to accumulation of unstudied organic impurities in the used absorbent solutions. These impurities reduce the drying capacity of triethylene glycol. In order to increase the effectiveness of installations for drying natural gas it is necessary to purify triethylene glycol from the accumulated impurities. The absence of information on the structure and properties of these impurities considerably complicates the purification of the absorbent solutions. In this study the structures of impurities accumulated in triethylene glycol were determined by NMR and high resolution mass-spectrometry coupled with chromatography (HPLC-MS/MS). The obtained results will enable to improve the existing methods for the purification of the working solutions of the absorbent.